Investigation of the D(3He, p)4He Reaction in the Astrophysical Energy Region of 18-30 keV; JETP Letters; Vol. 107, No. 11 - Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Penkov F. M. Fedor Mikhaylovich; Tuleushev Yu. Zh Yury Zhianshakhovich; Filipowicz M. Mariusz; Filippov A. V. Aleksandr Viktorovich (2018, 2018)
Title screen